PENERAPAN PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DALAM MEMBENTUK KARAKTER SISWA MADRASAH IBTIDAIYAH - Umi Nur Kholifatun; Riska Ramadani; Sulistiawati; Ulfayanti Ulfayanti; Wahyu Eka Saputra (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Character education is a crucial component in the implementation of education at Madrasah Ibtidaiyah (Islamic elementary schools), as it is oriented toward shaping students who are not only cognitively excellent but also possess good morals in accordance with Islamic teachings. In an era of rapid technological development and social change, various moral and behavioral challenges among children have also evolved, necessitating educational efforts capable of instilling character values effectively. In this context, the learning of Islamic Cultural History (Sejarah Kebudayaan Islam – SKI) plays a significant role as a means of character formation through the delivery of exemplary stories of the Prophet Muhammad (PBUH), his companions, and other Islamic figures that embody values of religiosity, honesty, responsibility, discipline, hard work, and tolerance. This study aims to examine the implementation of Islamic Cultural History learning in shaping the character of Madrasah Ibtidaiyah students and to identify the various character values instilled through the learning process. This research employs a library research method with a qualitative descriptive approach. Data were obtained through review and analysis of various relevant literature sources, such as books, scholarly articles, journals, and other supporting documents. The findings indicate that SKI learning, implemented through storytelling methods, role modeling, discussion, reflection, and habituation, can optimally facilitate the internalization of character values among students. Therefore, SKI learning not only serves as a medium for conveying knowledge about the historical development of Islam but also functions as an instrument of character education that supports the formation of Madrasah Ibtidaiyah students who are faithful, morally upright, and capable of applying Islamic values in their daily lives.